Echoes of a distant summer a novel - Johnson, Guy (Random House, 2002)
After the assassination of his grandfather, King Tremain, Jackson St. Clair Tremain takes over King's organization to protect his family, reflecting on the childhood summers he spent with King and the lessons he learned from his grandfather.